Vehicle-relocation optimization for one-way carsharing - Kim, Kyoung Hoon; Lee, Young Hoon (International Journal of Industrial Engineering: Theory, Applications and Practice, 2018)
Carsharing is becoming one of the fastest growing industries. In contrast to a round-trip system, the one-way carsharing system permits to return the rented vehicle to another station. Inevitably, a one-way system results in vehicle inventory imbalance issues and periodical vehicle relocations are required as a result. This paper deals with the issue using two optimization models: CArsharing NO relocation with MAximal demand satisfaction (CANOMA) and Carsharing RElocation with MAximal demand satisfaction (CREMA). The CANOMA model looks into the optimal solution of vehicle inventory and allocation without vehicle relocation, while the CREMA model searches for optimal solution of vehicle inventory, allocation and relocation with periodic vehicle relocation. Various experiments are performed to prove the vehicle relocation. In comparison with CANOMA, CREMA shows a lower level of vehicle inventory, a higher level of vehicle allocation and utilization required for meeting same customer demand via efficient vehicle relocation.